The Importance of Incorporating Service-Learning Projects into the Medical School Curriculum - Sohini Lahiri; Rama Abdin; Aviv Elimelech; Stephanie Salgueiro Massimilian; Peter Averkiou (University Library System, University of Pittsburgh, 2022)
ABSTRACT. The incorporation of Service-Learning Projects (SLPs) into the medical school curriculum is an effective way for students to adopt the leadership skills necessary to apply their traditional education on social determinants of health into targeted action. For our SLP, our team of second-year medical students organized an after-school science program to address the concerns of academically at-risk K-5th grade students at a local Non-Profit Organization (NPO). The goal was to increase interest in Science, Technology, Engineering, and Mathematic (STEM) subjects and careers. Our weekly lesson plans always utilized experimental learning models in an effort to foster engagement. Throughout the duration of the project, student participation grew to three-fold of the initial cohort. Through this SLP, we identified a disparity within our local community and developed a targeted solution to address this issue. We honed our skills not traditionally covered in a medical school curriculum, including program planning, fundraising, marketing, etc., and feel more capable taking on more significant leadership roles in the future. Additionally, our specific SLP provided us with an invaluable lesson in fostering communication skills that will benefit patient education.